Tier-specific evolution of match performance characteristics in the English Premier League: it's getting tougher at the top. Issue 10 (18th May 2016) - Bradley, Paul S.; Archer, David T.; Hogg, Bob; Schuth, Gabor; Bush, Michael; Carling, Chris; Barnes, Chris
Abstract: This study investigated the evolution of physical and technical performances in the English Premier League (EPL), with special reference to league ranking. Match performance observations ( n  = 14, 700) were collected using a multiple-camera computerised tracking system across seven consecutive EPL seasons (2006–07 to 2012–13). Final league rankings were classified into Tiers: (A) 1st–4th ranking ( n  = 2519), (B) 5th–8th ranking ( n  = 2965), (C) 9th–14th ranking ( n  = 4448) and (D) 15th–20th ranking ( n  = 4768). Teams in Tier B demonstrated moderate increases in high-intensity running distance while in ball possession from the 2006–07 to 2012–13 season ( P  < 0.001; effect size [ES]: 0.68), with Tiers A, C and D producing less pronounced increases across the same period ( P  < 0.005; ES: 0.26, 0.41 and 0.33, respectively). Large increases in sprint distance were observed from the 2006–07 to 2012–13 season for Tier B ( P  < 0.001; ES: 1.21), while only moderate increases were evident for Tiers A, C and D ( P  < 0.001; ES: 0.75, 0.97 and 0.84, respectively). Tier B demonstrated large increases in the number of passes performed and received in 2012–13 compared to 2006–07 ( P  < 0.001; ES: 1.32–1.53) with small-to-moderate increases in Tier A ( P  < 0.001; ES: 0.30–0.38), Tier C ( P  < 0.001; ES: 0.46–0.54) and Tier D ( P  < 0.001; ES: 0.69–0.87). The demarcation line between 4th (bottom of Tier A) and 5th ranking (top of Tier B) in the 2006–07 season was 8 points, but this decreased to just a single point in the 2012–13 season. The data demonstrate that physical and technical performances have evolved more in Tier B than any other Tier in the EPL and could indicate a narrowing of the performance gap between the top two Tiers.